Empirical models of trigonal distortions and polarization in perovskites. Issue 12 (14th August 2020) - Smith, Evan; Wander, Olivia; Ubic, Rick
Abstract: Correlative models derived from empirical relations describing synthesis‐structure relationships are essential to guiding and improving future research and development of functional materials, yet few models exist for the prediction of structural distortions in perovskites. In this work, a data‐mining approach has been employed to collect structural data for trigonally distorted perovskites in specific model systems. Correlative models were developed which describe the relationship between the c / a ratio and the ratio of the pseudocubic lattice constant ( a pc ) to the B‐X bond length ( r BX ). General models were then created for the c / a ratio in terms of the modified tolerance factor for trigonal perovskites with R 3 ¯ c symmetry and perovskite‐like compounds with R 3 c symmetry. These models accurately predict the lattice constants in trigonally distorted perovskites and LiNbO3 type perovskite‐like compounds. In addition, a general model was developed, which accurately predicts polarization in trigonal LiNbO3 type perovskite‐like compounds in space group R 3 c .